AL Amyloidosis for the Cardiologist and Oncologist - Ronald M. Witteles, MD; Michaela Liedtke, MD (JACC. CardioOncology, 2019)
AL amyloidosis results from clonal production of immunoglobulin light chains, most commonly arising from a clonal plasma cell disorder. Once considered a nearly uniformly fatal disease, prognosis has improved markedly over the past 15 years, predominantly because of advances in light chain suppressive therapies. Cardiac deposition of amyloid fibrils is common, and the severity of cardiac involvement remains the primary driver of prognosis. Improvements in chemotherapy/immunotherapy have prompted a reassessment of the role of advanced cardiac therapies previously considered contraindicated in most patients, including the role of implantable cardioverter-defibrillators and cardiac transplantation. This state-of-the-art review highlights the current state of the field, including diagnosis, prognosis, and hematologic- and cardiac-specific therapies.